From object to encounter: Aesthetic politics and visual criminology. (May 2014) - Young, Alison
Recent criminological research has engaged with images of crime such that there increasingly appears to exist a need for a specifically visual criminology. Within visual criminology, however, images are frequently constructed as objects of analysis rather than as constitutive elements of the discursive field. This article draws upon the specific context of the social, cultural and legal responses to uncommissioned words and images in public space—street art and graffiti writing. Focusing on one instance of unauthorized image making, I argue for the dynamic role of the image in the constitution of crime in contemporary society and culture, thanks to the affective dimension of the encounter between spectator and image. The complex range of responses to street art and graffiti highlights ways in which visual criminology must ensure that it eschews an object-centred approach to the image, and conceptualize it instead by means of an aesthetic politics of the encounter.